2024
DOI: 10.1101/2024.06.07.597709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applicability of epigenetic age models to next-generation methylation arrays

Leonardo D. Garma,
Miguel Quintela-Fandino

Abstract: BackgroundEpigenetic clocks based on DNA methylation data are routinely used to obtain surrogate measures of biological age and estimate epigenetic age acceleration rates. These tools are mathematical models that rely on the methylation state of specific sets of CpG islands quantified using microarrays. The set of CpG islands probed in the microarrays differed between the models. Thus, as new methylation microarrays are developed and older models are discontinued, existing epigenetic clocks might become obsole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The newly developed Illumina EPICv2 microarray provides wider coverage of the DNA methylome compared to its predecessor EPICv1, with some reported differences in overall probe content. While good correlations between the two EPIC versions have been previously reported [5][6][7], a recent study demonstrated that differing probe content between versions influences epigenetic age estimates, although this was not evaluated in matched samples profiled on EPICv1 and EPICv2 [42]. To that end, we measured DNA methylation on EPICv1 and EPICv2 in matched venous blood samples from adults across three geographically diverse populations, and comprehensively examined the concordance between versions in a wide range of DNA methylation-based tools.…”
Section: Discussionmentioning
confidence: 99%
“…The newly developed Illumina EPICv2 microarray provides wider coverage of the DNA methylome compared to its predecessor EPICv1, with some reported differences in overall probe content. While good correlations between the two EPIC versions have been previously reported [5][6][7], a recent study demonstrated that differing probe content between versions influences epigenetic age estimates, although this was not evaluated in matched samples profiled on EPICv1 and EPICv2 [42]. To that end, we measured DNA methylation on EPICv1 and EPICv2 in matched venous blood samples from adults across three geographically diverse populations, and comprehensively examined the concordance between versions in a wide range of DNA methylation-based tools.…”
Section: Discussionmentioning
confidence: 99%